BIBLIOMETRIA APLICADA AO USO DE CÂMARAS CLIMÁTICAS EM ESTUDOS DE CONFORTO AMBIENTAL - Tamura, Cintia Akemi; Ribeiro, Daniele Abe; Trevisan, Livia Yu Iwamura; Krüger, Eduardo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Climate chambers (CC) allow experimenters to control environmental variables, making it possible to carry out studies on occupant behavior and perception, the built environment and the interrelations between these areas. Considering the scope and multidisciplinary nature of the area, a bibliometric survey was carried out on CC, aiming to classify dominant fields of study and the main terms associated to it. In this paper, bibliometric techniques are used from a sample of 3909 articles obtained from the Web of Science repository in November 2017, for the time period 2012-2017. Four terms usually associated with CC were identified: "Climate + chamber"; "Climatic + chamber"; "Environmental + chamber" and "Test + chamber". The most representative research topics were identified and Keyword Maps generated with VOSviewer, from which interactions between terminologies and study areas could be observed.